The formative period of Islamic thought - Watt, W. Montgomery (Oneworld, 2006)
This text gives a formative account of the development of Islamic thought from the death of Muhammad in 632, to 950. It demonstrates how various religions and political movements within Islam contributed to what has become standard form, including the positive contribution of sects later regarded as heretical, and the key interaction of religion and politics. Drawing on many previously unresearched Arabic sources, it presents a comprehensive, balanced and clear picture of the main lines of philosophical development in this important period.